A Qualitative Study of Nursing Students' Experiences in Fall Prevention for Older Home Care Clients. (28th June 2020) - Turjamaa, Riitta; Äijö, Marja; Tervo-Heikkinen, Tarja; Silén-Lipponen, Marja
Abstract : The aim of this study was to describe the experiences of nursing students in fall prevention during clinical practice in the context of older home care clients. This was a qualitative focus group study of nursing students ( n  = 9) who had completed clinical practice in older clients' home care. The data were analysed using inductive content analysis. The nursing students described their experiences regarding falls and fall prevention in older clients' home care from two perspectives: evaluation of falls at older people's homes and fall prevention during home visits. Systematic evaluation of falls was based on physical examination and is the basis of fall prevention. However, evaluation of nutrition and adverse drug effects seemed to be ignored. In addition, fall prevention during home visits included concrete fall prevention in authentic client situations, confidential relationships with older clients, and evidence-based knowledge. From the perspective of fall prevention, there was a lack of comprehensive evaluation and understanding of the meaning of psychological factors, such as fear of falling. In order to be able to prevent falls in the older client population, students need more guidance regarding a comprehensive approach based on evaluation of falls. In addition, there is a need for continuous collaboration between education and home care services to develop educational approaches that interlink knowledge and skills in fall prevention.